Oxoborane (RBO) Complexation and Concomitant Electrophilic Bond Activation Processes. Issue 36 (9th June 2017) - Swarnakar, Anindya K.; Hering‐Junghans, Christian; Ferguson, Michael J.; McDonald, Robert; Rivard, Eric
Abstract: Donor–acceptor complexes of the oxoboranes ClB=O and HOB=O were synthesized and each feature short multiply bonded B=O linkages. The retention of high Lewis acidic character within these encapsulated monomeric oxoboranes was manifested by their ability to support C−F and Si−O bond activation/functionalization. The reported ClB=O complexes can be regarded as synthetic surrogates of the [BO] + cation, an inorganic analogue of CO. Abstract : Giving a HO−B=O a home : A general donor–acceptor stabilization protocol is used to isolate Cl−B=O and HO−B=O complexes, and promote the electrophilic activation of C−F and Si−O bonds.